2010
DOI: 10.4141/cjas10019
|View full text |Cite
|
Sign up to set email alerts
|

Energy and nutrient digestibility in a hulless low-phytate phosphorus barley fed to finishing pigs

Abstract: . 2010. Energy and nutrient digestibility in a hulless low-phytate phosphorus barley fed to finishing pigs. Can. J. Anim. Sci. 90: 393Á399. Six-ileal cannulated finishing barrows were used to determine energy and nutrient digestibility in a sample of a hulless low-phytate (LP) barley cultivar. A sample of regular hulled (RH) barley was also included for comparison. Two diets containing 96.5% of either LP or RH barley, 2.5% trace minerals and vitamins and 1% indigestible marker (Celite) were fed in a twoperiod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
5
4
0
Order By: Relevance
“…The SID of CP and most AA estimated by regression analysis were in the range of SID values in barley reported in other studies (Hennig et al, 2006;Ige et al, 2010), and corresponded (95% confidence intervals) to SID values reported by NRC (2012) and AFZ et al (2000). (Eklund, 2006).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The SID of CP and most AA estimated by regression analysis were in the range of SID values in barley reported in other studies (Hennig et al, 2006;Ige et al, 2010), and corresponded (95% confidence intervals) to SID values reported by NRC (2012) and AFZ et al (2000). (Eklund, 2006).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, nutrient digestibility of barley in pigs can be substantially reduced (O'Connell et al, 2005). Moreover, less interaction between diet and digestive enzymes may result in increased specific ileal endogenous losses of CP and AA, as digesta viscosity inhibits sufficient interaction between (Chesson, 1993; Nyachoti et al, 2000;Jansman et al, 2002).The SID of CP and most AA estimated by regression analysis were in the range of SID values in barley reported in other studies (Hennig et al, 2006;Ige et al, 2010), and corresponded (95% confidence intervals) to SID values reported by NRC (2012) and AFZ et al (2000). (Eklund, 2006).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The GE values for the tested pea varieties were similar to the value reported by NRC (2012). The N and AA contents in the tested LPB were similar to literature values (Thacker et al, 2003;Ige et al, 2010) but the GE value determined in the current study was slightly lower than the values of 16.75 and 17.02 MJ/kg reported by Veum et al (2007) and Ige et al (2010), respectively, for LPB. The total P content in LPP 4.3 (g/kg) and NPP (4.7 g/kg) and were close to the values of 4.2 g/kg reported by NRC (2012) and 4.4 g/kg reported by Stein (2006).…”
Section: Discussionsupporting
confidence: 53%
“…Low-phytate cereal grains were introduced in the late 1990s with corn, barley and rice being the first low-phytate cereals grains to be developed (Raboy, 2002). Various studies have shown that low-phytate corn and barley have higher P digestibility which is attributed to their increased content of non-phytate-bound P (Spencer et al, 2000;Thacker et al, 2004;Bohlke et al, 2005;Ige et al, 2010). Recently, low-phytate field pea lines were developed at the University of Saskatchewan's Crop Development Centre (Saskatoon, SK, Canada) with a total P content of 3.28-5.56 mg/kg and inorganic P content of 1.00-1.08 mg/kg (Delgerjav et al, 2011).…”
Section: Discussionmentioning
confidence: 98%